Research of underground positioning algorithm based on DOA and TDOA - ZHAI Yan-rong; HUANG Huan; ZHANG Shen; MA Xiu-ping; LIU Wei; YOU Chun-xia (Gong-kuang zidonghua, 2013)
In view of problems that current underground positioning system is sensitive to environmental change and has low positioning accuracy, the paper introduced an underground positioning algorithm based on DOA and TDOA. The algorithm takes advantages of high accuracy of TDOA and high angular resolution of DOA, uses weighted average of respective direction angle of DOA and TDOA as signal angle, and combined with radius got by TDOA algorithm to calculate coordinates of mobile terminal. The simulation results show that the algorithm can achieve stable performance and high positioning accuracy in complex environment.